KASL clinical practice guidelines for management of chronic hepatitis B (Clinical and molecular hepatology, 2019)
Information about the committee and funds The Committee for the Revision of Clinical Practice Guidelines for CHB 2018, launched in accordance with the initiative of the Board of Directors of the KASL and approved by the council, was composed of ten hepatologists. Levels of evidence and grades of recommendation The collected data were analyzed through a systematic review, and the levels of evidence were classified by the revised Grading of Recommendations, Assessment, Development and Evaluation (GRADE) system. Grading of Recommendations, Assessment, Development and Evaluation (GRADE) Criteria Quality of evidence  High (A) Further research is unlikely to change confidence in the estimate of the clinical effect.  Moderate (B) Further research may change confidence in the estimate of the clinical effect.  Low (C) Further research is very likely to impact confidence on the estimate of clinical effect. Duration of these phases varies, sequences of phases are not continuous in patients, and there can be a gray zone in which the features are not compatible with any specific phase. [...]assigning phases of infection or making a decision regarding antiviral treatment based on a single alanine aminotransferase (ALT) and HBV DNA is insufficient (Fig. 1) [4].